1995
DOI: 10.1192/bjp.167.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Families Coping with Schizophrenia Behavioural Family Intervention v. Case Management with a Low-Income Spanish-Speaking Population

Abstract: Sociocultural factors affect responses to different types of intervention. The results did not support earlier findings of a beneficial effect of BFM when applied to a socioculturally diverse population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
81
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 13 publications
5
81
2
Order By: Relevance
“…The one study that made cross cultural comparisons identified older age for monolingual Spanish-speaking Latinos and more years of past treatment and fewer depressive symptoms for Euro-Americans as predictive of higher adherence (56). Nonadherence was found to predict worsened illness course in the two studies examining the health-related outcomes of nonadherence (42, 43). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The one study that made cross cultural comparisons identified older age for monolingual Spanish-speaking Latinos and more years of past treatment and fewer depressive symptoms for Euro-Americans as predictive of higher adherence (56). Nonadherence was found to predict worsened illness course in the two studies examining the health-related outcomes of nonadherence (42, 43). …”
Section: Resultsmentioning
confidence: 99%
“…Study objectives varied, with some focusing specifically on adherence (1, 6, 41, 4447, 49, 5160) while others measured adherence as part of studies addressing different questions. Geographically, eight were based in California (6, 42, 43, 47, 48, 50, 54, 55), two in Texas (41, 51), one in New Mexico (52), one in New York (49), one in Connecticut (56), one in Ohio (40), and four were from Veteran’s Administration National Registries (46, 5860), and three were national studies (1, 45, 57). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations